Internalising 'sensitivity': vulnerability, reflexivity and death research(ers). Issue 5 (3rd September 2021) - Borgstrom, Erica; Ellis, Julie
ABSTRACT: Research about dying is viewed as inherently sensitive because of how death is perceived in many societies. Such framing assumes participants are 'vulnerable' and at risk of 'harm' from research. Simultaneously, with increasing recognition of the importance of reflexivity, researchers can become (deeply) preoccupied with their actions and experiences in the field. Whilst reflexivity is often described as a helpful process, in this paper we consider when introspection becomes problematic and even harmful for death researchers, in both a professional and personal sense. Identifying a process we call 'internalising sensitivity' the paper describes our own experiences of working and living with the pervasive ethical notions of sensitivity, vulnerability, risk and harm. We argue that these discourses can get 'under the skin' of researchers in that they impact researchers intellectually, emotionally, and physically, and this in turns affects their relationship with the research process and their place within, and beyond it.